A COMPARATIVE ANALYSIS OF THE ASSORTMENT OF DIFFERENT MEDICATION GROUPS USED IN THE CENTRAL REGIONAL HOSPITAL OF THE MUNICIPAL REGION AND THE REGIONAL HOSPITAL OF THE FEDERAL STATE-OPERATED HEALTHCARE AGENCY “MEDICAL AND SANITARY CENTER-23” (FKUZ MSCH-23) OF THE FEDERAL PENITENTIARY SERVICE (FSIN) OF RUSSIA - B. G. Bochkarev; I. V. Kalinin; T. I. Kabakova (Фармация и фармакология (Пятигорск), 2018)
Providing quality pharmaceutical care is a key task of healthcare; any medical organization must respond efficiently to a change in both external and internal factors that affect the medical support of patients. The aim of this study was to analyze the structure of medication consumption in comparable hospitals in the penitentiary and civilian healthcare systems. Materials and methods. The study was conducted on the basis of content analysis, documentary observation, ABC analysis, and comparison of performance indicators of medical organizations. Results and discussion. This study analyzed the assortment of commodity stocks of medications in the regional clinical hospital that is a part of the structure of FSIN and a typical central regional hospital (CRH). Using ABC analysis it was established that the Group A (the most costly) medications in the penitentiary medical organization consisted exclusively of anti-viraldrugs used for treating HIV-infected patients, which is 54.91% of the stock that are represented by 18 international non-proprietary medication names. In turn, Group A of the medication assortment of the State Budgetary Healthcare Organization of the Republic of Adygea (GBUZ RA) “Krasnogvardeiskaia CRH” consists of three pharmacological groups – plasma substitutes, cardiovascular medications, and antibiotics. On the basis of the obtained data, the study identified different groups of medications and studied their assortment based on international non-proprietary namesand medication forms that received preference either in the branch of Clinical Hospital-2 (KB-2) FKUZ MSCh-23 FSIN of Russia or GBUZ RA “Krasnogvardeiskaia CRH” (38 ATC groups in all). The first group consists of medications from the following 12 ATC groups (31.6%), the assortment of which can be found exclusively in the branch of “KB-2” FKUZ MSCh-23 of the Federal Penitentiary Service of Russia: antiretroviral, muscle relaxants, anticonvulsants, adaptogens, antidepressants) or significantly exceeds similar stocks in GBUZ RA “Krasnogvardeiskaia CRH”: anti-asthmatic agents (3 times), anti-fungal drugs (3 times), hormones except for insulin (2.2 times), respiratory regulators (2 times), non-steroidal anti-inflammatory drugs (1.7 times), medications regulating the gastrointestinal function (1.5 times), and antibacterial agents (1.4 times). The second group consists of medications of the following 9 ATC groups (23.7%) that are stocked only by GBUZ RA “Krasnogvardeiskaia CRH”: antifermental drugs, radiocontrast agents, chondroprotective and antiparasitic medications, and -- within a wider diapason of non-proprietary drugs and forms of manufacture – diuretics (5 times), antitubercular (3 times), antiviral with the exception of anti-HIV (2 times), spasmolytics (2 times), and hypertension drugs (1.5 times). It was determined that the main medical activity of medical organizations subordinate to FSIN of Russia, is aimed at treatment and prevention of complications of the most socially dangerous diseases – HIV/AIDS and tuberculosis – as well as therapy of the associated diseases. It was shown that pharmacists do not use methods of pharmacological-economic analysis in their work, and the medication needs of medical organizations are only 20% satisfied. Conclusion. The identified shortcomings attest to the need to develop and implement a more effective system for the formation of stockpiles in the pharmacies of the penitentiarymedical organization.